Answer:
The circumference of the circle
Step-by-step explanation:
Step-by-step explanation:
we see the common difference is
a2-a1 = 11x + 9 - 4x - 5 = 7x + 4
an = an-1 + (7x+4) = a1 + (n-1)×(7x+4)
for a7 we have then
a7 = 4x + 5 + 6×(7x +4) = 4x + 5 + 42x + 24 = 46x + 29
Answer:
D. y - 7 = -4 (x - 2)
Step-by-step explanation:
y - 7 = -4 (x - 2)
7. tails, odd, 4
P(tails) = 1/2
P(odd) = 3/6 = 1/2
P(4) = 1/6
P(tails then odd then 4) = (1/2)×(1/2)×(1/6) = 1/24 ≈ 0.041666
Answer: 1/24, 4.2%
8. tails, 6 or 1, 3
P(6 or 1) = 2/6 = 1/3
P(3) = 1/6
P( tails, 6 or 1, 3) = (1/2)(1/3)(1/6) = 1/36 ≈ 0.027777
Answer: 1/36, 2.8%
9. heads, not 2, even
P(heads) = 1/2
P(not 2) = 5/6
P(even) = 1/2
P(heads, not 2, even) = (1/2)(5/6)(1/2) = 5/24 ≈ 0.208333
Answer: 5/24, 20.8%